2021
DOI: 10.25259/ijdvl_963_19
|View full text |Cite
|
Sign up to set email alerts
|

Management of Darier disease: A review of the literature and update

Abstract: Darier disease (DD) is a rare type of inherited keratinizing disorder with no definitive therapeutic approach. The objective of this study is to provide a detailed literature review of all the available treatment modalities of Darier disease, including those that are both surgical and non surgical, to compare their efficacies and to propose a novel therapeutic approach. A complete search of the literature for all articles describing the different treatments of Darier disease, with no restrictions on patients’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 85 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…Darier’s disease is a relatively rare autosomal dominant genodermatosis, with a prevalence of 1 in 30,000 to 100,000 people and no gender difference. 1 , 6 In addition to the manifestation of hyperkeratotic papules in seborrheic or intertriginous areas, DD manifests with warty papules on the dorsum of hands and feet, palmoplantar pits, and longitudinal red or white stripes in the fingernails. 6 These findings were not presented by the present case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Darier’s disease is a relatively rare autosomal dominant genodermatosis, with a prevalence of 1 in 30,000 to 100,000 people and no gender difference. 1 , 6 In addition to the manifestation of hyperkeratotic papules in seborrheic or intertriginous areas, DD manifests with warty papules on the dorsum of hands and feet, palmoplantar pits, and longitudinal red or white stripes in the fingernails. 6 These findings were not presented by the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Darier’s disease is an intractable disease for which there are no proven curative treatments. 1 It was recently reported that a low dose (1–5 mg/d) of opioid receptor antagonist naltrexone improved the mild-to-moderate forms of the clinical manifestation in patients with DD 12 and may become a new treatment option by possibly affecting inflammation, desmosomal adhesion, or migration of keratinocytes. 13 According to the comprehensive review of the literature on therapeutic options for DD, 14 there was grade B evidence (weak recommendation; limited-quality, patient-oriented evidence) supporting the efficacy of topical 1,25-dihydroxyvitamin D3 analogs, whereas there was grade C evidence (weak recommendation; low-quality evidence) for the use of fluocinonide, a corticosteroid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concomitant application of topical retinoids could be useful, and in some cases, oral retinoids, either acitretin or isotretinoin, could be prescribed. The use of topical corticosteroids could reduce inflammation but do not alter the disease course 6 . The apathetic behavior and the low interest about medical condition, in association with the dysthymia, could represent a factor of poor adherence to both dermatologic and psychiatric therapy.…”
Section: Discussionmentioning
confidence: 99%